2020
DOI: 10.21203/rs.3.rs-48111/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fighting the Bite during a Crisis: Capabilities of Florida Mosquito Control Districts during the COVID-19 Pandemic

Abstract: Background: The national wide lockdown order imposed in early April 2020 due to the COVID-19 pandemic complicated mosquito control activities across the United States (US), and Florida is no exception. Mosquito control programs are the first line of defense against mosquitoes-borne pathogens in the state of Florida. The purpose of this study was to examine the capabilities of Florida mosquito programs to implement key mosquito measures during the COVID-19 pandemic.Methods: In a self-administered online survey,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This study explored the capability and preparedness of US refugee resettlement agencies to provide services to clients during the COVID-19 pandemic. Like our previous study [11], we observed that US refugee resettlement agencies continued to perform despite a lack of funding. This posture can be attributed to the professional predisposition of refugee resettlement agencies to helping the underserved, regardless of capacity or funding levels.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study explored the capability and preparedness of US refugee resettlement agencies to provide services to clients during the COVID-19 pandemic. Like our previous study [11], we observed that US refugee resettlement agencies continued to perform despite a lack of funding. This posture can be attributed to the professional predisposition of refugee resettlement agencies to helping the underserved, regardless of capacity or funding levels.…”
Section: Discussionsupporting
confidence: 80%
“…However, the stay-at-home order necessitated by the pandemic affected the delivery of and access to healthcare not only globally [2][3][4], but also across the US (beginning March 21, 2020). In US healthcare, for example [5], the most affected service delivery systems include those that focus on children's welfare [6], psychiatric care [7], community outreach and behavioral health [8][9][10], and arbovirus surveillance programs [11]. In Ohio, COVID-19 caused a disruption of health and social services systems, and a decrease in volunteer availability for volunteer-dependent agencies [12].…”
Section: Introductionmentioning
confidence: 99%